The milk of dreams = Il latte dei sogni: Biennale arte 2022 - Biennale di Venezia (59e : 2022 : Venise, Italie); Alemani, Cecilia (La Biennale di Venezia, 2022)
The colossal two-part catalog accompanying the 2022 biennial’s ambitious exploration of metamorphosis, as imagined by 213 artists from across the world Named after a children’s book by Surrealist artist Leonora Carrington, the 59th Venice Biennale takes Carrington’s fey creatures, along with other figures of transformation, as companions on an imaginary journey through the metamorphoses of bodies and slippery definitions of humanity. Volume I of this two-part publication addresses the conceptual basis of The Milk of Dreams, as developed by curator Cecilia Alemani, and further elaborates upon its thematic threads. Each artist from the 2022 Biennale is introduced by way of a critical text and an iconographic apparatus. The volume includes Alemani’s original exhibition texts and a plethora of original essays by some of today’s most cutting-edge thinkers and writers, with conversations and reprinted texts concerning the exhibition: the representation of bodies and their metamorphoses, the relationship between individuals and technologies, and the connection between bodies and the earth. Volume II of the catalog presents the participating countries and the collateral events of the biennale; its lavishly illustrated texts explore the various projects on display in Venice. Artists include: Sophia Al-Maria, Josephine Baker, Djuna Barnes, Jadé Fadojutimi, Nan Goldin, Robert Grosvenor, Tishan Hsu, Jacqueline Humphries, Allison Katz, Kapwani Kiwanga, Barbara Kruger, Hannah Levy, Liliane Lijn, Candice Lin, Precious Okoyomon, Akosua Adoma Owusu, Elle Pérez, Aki Sasamoto, Sable Elyse Smith, Kaari Upson, Andra Ursuta, Cecilia Vicuña, Marianne Vitale, Meta Vaux Warrick Fuller and Laura Wheeler Waring.
Keywords: art contemporain; arts; arts visuels et médiatiques; corps; cours; discipline; har4600; histoire de l'art; premier cycle; thématiques

279 / Paul B. Preciado. Le plaisir-savoir - St-Gelais, Thérèse; Pignedoli, Clark (Spirale, 2022)
Philosophe et commissaire au parcours militant, Paul B. Preciado est l’un des penseur·e·s contemporain·e·s qui a le plus contribué à l’articulation des mouvements de la pensée queer et trans/féministe. Comme le soulignent Thérèse St-Gelais et Clark Pignedoli, qui ont dirigé ce dossier consacré à son travail : « Preciado représente une figure de médiation et de traduction entre des épistémologies et des cultures de genre et sexuelles différentes, il est un tisseur d’alliances et de complicités transnationales. » C’est en revisitant le concept de plaisir-savoir, présent dans l’ensemble de l’œuvre de Preciado, que les auteurs et autrices de ce dossier dialoguent avec les écrits et les pratiques du philosophe-commissaire, afin d’explorer des voies alternatives pour réfléchir le savoir, la langue, le désir, qui passent par un désapprentissage des normes.
Keywords: LGBTQIA2+; amour; approches et analyses; arts; autofiction; corps; cours; discipline; har4600; histoire de l'art; identités LGBTQIA2+; philosophie; plaisir-savoir; premier cycle; queer; ressource en ligne; sciences humaines; thématiques; transféminisme